2020
DOI: 10.1080/16549716.2020.1803543
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to the uptake of childhood vaccination in Galkayo District, Puntland, Somalia

Abstract: Background: As in many Sub-Saharan African countries, the health system in Somalia is not operating at the capacity needed to lift childhood vaccination coverage to ninety percent or above, as recommended by United Nations Children's Fund. Current national estimates of coverage for the six major vaccine preventable childhood diseases range from thirty to sixty percent. Infectious disease outbreaks continue to pose significant challenges for the country's health authorities. Objective: This important qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
(84 reference statements)
1
16
0
Order By: Relevance
“…With all other variables adjusted, multivariate analysis revealed that parental mistrust of domestic vaccines was one of the main risk factors for vaccine hesitancy in Guangzhou. A study on the factors affecting childhood vaccination in Galkayo District, Puntland, Somalia showed that parents’ low trust in vaccines could not be ignored, 31 while vaccine safety was one of the main factors that affected parents’ trust in vaccines. From 2016 to 2018, the reported vaccine safety incidents attracted significant attention in China.…”
Section: Discussionmentioning
confidence: 99%
“…With all other variables adjusted, multivariate analysis revealed that parental mistrust of domestic vaccines was one of the main risk factors for vaccine hesitancy in Guangzhou. A study on the factors affecting childhood vaccination in Galkayo District, Puntland, Somalia showed that parents’ low trust in vaccines could not be ignored, 31 while vaccine safety was one of the main factors that affected parents’ trust in vaccines. From 2016 to 2018, the reported vaccine safety incidents attracted significant attention in China.…”
Section: Discussionmentioning
confidence: 99%
“…This disrupts vaccination programs and prevents children from being fully vaccinated. 19 Restoration of routine immunizations takes long because of the destruction of health care facilities during wars. For example, DRC Congo continues experiencing conflicts between the armed militia groups, FDLR and Mai Mai militia.…”
Section: The Following Are Among the Factors That Influencing Childhood Vaccine Uptakementioning
confidence: 99%
“…Thus, labour pain is perceived as a normal life journey by most women and midwives [ 3 , 4 ]. Labour pain is caused by uterine muscle contractions and pressure exerted by presenting part of the fetus against the maternal pelvis, urinary bladder, and bowel during the passage of the fetus through the birth canal [ 5 , 6 ]. Loneliness, ignorance, unkind or insensitive treatment during labour, along with unresolved past psychological or physical distress, increases the chance that the woman will suffer.…”
Section: Introductionmentioning
confidence: 99%